Mind Wandering While Driving: What Does it Mean and What do we do about it?. (September 2015) - Lerner, Neil; Baldwin, Carryl; Higgins, J. Stephen; Lee, John; Schooler, Jonathan
Distracted driving has been identified as a major concern in highway safety. Research to-date, however, has largely focused on distraction related to external events or intentional engagement in non-driving activities. Internal distraction ("mind wandering") is now being recognized as a significant source of driver distraction that requires rigorous study. There are substantial challenges in detecting, measuring, and addressing mind wandering while driving. Panelists with expertise in driver distraction in general, and mind wandering in particular, will discuss both scientific and pragmatic issues in addressing this problem. Each panelist will present a brief perspective on the problem from the point of view of their experience and expertise. This will be followed by an open discussion period.